2021
DOI: 10.1002/ecs2.3730
|View full text |Cite
|
Sign up to set email alerts
|

Season of prescribed fire determines grassland restoration outcomes after fire exclusion and overgrazing

Abstract: Fire exclusion and mismanaged grazing are globally important drivers of environmental change in mesic C 4 grasslands and savannas. Although interest is growing in prescribed fire for grassland restoration, we have little long-term experimental evidence of the influence of burn season on the recovery of herbaceous plant communities, encroachment by trees and shrubs, and invasion by exotic grasses. We conducted a prescribed fire experiment (seven burns between 2001 and 2019) in historically fire-excluded and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…The fire regime in this study included burning every year in early spring and was used to mimic the most recent anthropogenic use of fire, which was annually burning of meadows for improved pasture for livestock . The high reduction of woody vegetation in our spring fires somewhat contradicts results from other studies that found a higher mortality in late summer fires, due to higher fire intensity (Ansley et al, 2021;Laris et al, 2021;N'Dri et al, 2022;Novak et al, 2021). However, since all present trees were removed at the start of our experiment, there were only newly resprouted seedlings and saplings that were exposed to fire, and as discussed in Paper I, it takes time for trees to develop traits to survive fire, such as thick bark .…”
Section: Fire and Herbivory Suppress Tree Recruitment And Promote Gra...contrasting
confidence: 76%
“…The fire regime in this study included burning every year in early spring and was used to mimic the most recent anthropogenic use of fire, which was annually burning of meadows for improved pasture for livestock . The high reduction of woody vegetation in our spring fires somewhat contradicts results from other studies that found a higher mortality in late summer fires, due to higher fire intensity (Ansley et al, 2021;Laris et al, 2021;N'Dri et al, 2022;Novak et al, 2021). However, since all present trees were removed at the start of our experiment, there were only newly resprouted seedlings and saplings that were exposed to fire, and as discussed in Paper I, it takes time for trees to develop traits to survive fire, such as thick bark .…”
Section: Fire and Herbivory Suppress Tree Recruitment And Promote Gra...contrasting
confidence: 76%
“…In addition to light grazing, the absence of fire, particularly in abandoned fertile fields surrounded by woody vegetation in humid environments, accelerates the succession to a state of increased woody cover [84]. Bobrovsky and Khanina [85] also found that the absence of fire after abandonment results in a homogenous high-density distribution of pioneer woody species, while frequent fires maintain the succession at weedy stages for decades.…”
Section: Firementioning
confidence: 99%
“…On the other hand, fire in the early stage of succession has been reported to divert the succession pattern by arresting the development towards woody vegetation resulting in dwarf shrubs [86]. Even though Novak et al [84] concludes that prescribed burns benefit restoration by arresting bush encroachment and controlling invasive herbaceous species, they must be used with other strategies, such as introducing planting propagules for effective restoration. Therefore, the use of fire-tolerant grass species in reseeding and over-sowing initiatives will quicken the restoration process.…”
Section: Firementioning
confidence: 99%
“…Changes in fire frequency and elevated levels of carbon dioxide, either acting individually or interactively, are the main driving forces of bush encroachment (D'Odorico et al, 2012; Hudak, 1999; Van Auken, 2000). Bush encroachment can be accelerated by high livestock grazing pressure without resting the rangeland, leading to a reduction in grass fuel load needed for rangeland fire enhancement, thereby reducing the intensity and frequency of wildfires (Novak et al, 2021). Most bushes use C 3 photosynthetic pathway, while the majority of the herbaceous species in the rangelands are C 4 (D'Odorico et al, 2012; Orange‐Senqu River Commission (ORASECOM), 2013).…”
Section: Introductionmentioning
confidence: 99%